Decidere per chi non può Approcci filosofici all'eutanasia non volontaria - Galletti, Matteo (Studi e saggi, 2005)
For centuries, the philosophical thought has questioned notions such as "person", "value" and "quality" of life, "rights", "suffering", "life", "death"; but the problems that have arisen in recent decades due to the application of life-prolonging technologies have led to a rethinking of the philosophical and everyday meanings and uses of these notions. This book intends to be a reflection on some aspects of the debate on the moral lawfulness of non-voluntary euthanasia, through a critical discussion of the main philosophical notions used by bioethics.